ROPGAP-dependent interaction between brassinosteroid and ROP2-GTPase signaling controls pavement cell shape in Arabidopsis - Zhang, Cheng; Lauster, Theresa; Tang, Wenxin; Houbaert, Anaxi; Zhu, Shanshuo; Eeckhout, Dominique; De Smet, Ive; De Jaeger, Geert; Jacobs, Thomas B.; Xu, Tongda; Müller, Sabine; Russinova, Eugenia (Current Biology, 2022)
The epidermal pavement cell shape in Arabidopsis is driven by chemical and mechanical cues that direct partitioning mechanisms required for the establishment of the lobe- and indentation-defining polar sites. Brassinosteroid (BR) hormones regulate pavement cell morphogenesis, but the underlying mechanism remains unclear. Here, we identified two PLECKSTRIN HOMOLOGY GTPase-ACTIVATING proteins (PHGAPs) as substrates of the GSK3-like kinase BR-INSENSITIVE2 (BIN2). The phgap1phgap2 mutant displayed severe epidermal cell shape phenotypes, and the PHGAPs were markedly enriched in the anticlinal face of the pavement cell indenting regions. BIN2 phosphorylation of PHGAPs was required for their stability and polarization. BIN2 inhibition activated ROP2-GTPase signaling specifically in the lobes because of PHGAP degradation, while the PHGAPs restrained ROP2 activity in the indentations. Hence, we connect BR and ROP2-GTPase signaling pathways via the regulation of PHGAPs and put forward the importance of spatiotemporal control of BR signaling for pavement cell interdigitation.<br
Keywords: Brassinosteroid hormones; BIN2; PHGAP; ROP2; phosphorylation; pavement cell shape